2021
DOI: 10.1029/2021jc017354
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Composition of Sand and Mud Suspensions in Coastal and Estuarine Environments Using Combined Optical and Acoustic Measurements

Abstract: Quantifying and characterizing suspended sediment is essential to successful monitoring and management of estuaries and coastal environments. To quantify suspended sediment, optical and acoustic backscatter instruments are often used. Optical backscatter systems are more sensitive to mud particles (< 63µm) and flocs, whereas acoustic Accepted ArticleThis article is protected by copyright. All rights reserved.Confidential manuscript submitted to JGR-Oceans allows us to estimate whether there are more sand or mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 91 publications
1
14
0
Order By: Relevance
“…We can simplify this to an overall constant mud concentration, regardless of the local mud content in the bed, whereas sand concentrations in the water column would decrease with increasing mud content in the bed. This is supported by the findings of Colosimo et al ( 2020) and Pearson et al (2021), combined with the fact that muddy beds mainly prevail in calm environments. In the next section we test this simplification of the deposition fluxes, for the Wadden Sea and for tidal basins in general, and we explore its relevance for the observed bimodality of p mud in the sediment bed.…”
Section: Deposition Of Sand-mud Mixturessupporting
confidence: 73%
See 2 more Smart Citations
“…We can simplify this to an overall constant mud concentration, regardless of the local mud content in the bed, whereas sand concentrations in the water column would decrease with increasing mud content in the bed. This is supported by the findings of Colosimo et al ( 2020) and Pearson et al (2021), combined with the fact that muddy beds mainly prevail in calm environments. In the next section we test this simplification of the deposition fluxes, for the Wadden Sea and for tidal basins in general, and we explore its relevance for the observed bimodality of p mud in the sediment bed.…”
Section: Deposition Of Sand-mud Mixturessupporting
confidence: 73%
“…(2020) and Pearson et al. (2021), combined with the fact that muddy beds mainly prevail in calm environments. In the next section we test this simplification of the deposition fluxes, for the Wadden Sea and for tidal basins in general, and we explore its relevance for the observed bimodality of p mud in the sediment bed.…”
Section: Theoretical Analysis On the Bed Sediment Compositionmentioning
confidence: 97%
See 1 more Smart Citation
“…Conversely, mud in the distal samples was likely freshly deposited after Storm Sebastian, several days prior to their collection. Pearson et al (2021a) demonstrated that mud is regularly found in suspension over the sandy bed of the delta, even if it does not There is no trend in sorting with either ρ or θ, but 80% of samples are well sorted (0.35 < σ < 0.5 based on the Logarithmic Folk and Ward graphical measure (Blott and Pye, 2001). Moderately sorted samples (0.5 < σ < 1) tend to be located on the distal edge of the delta, while the most poorly sorted samples (σ > 1) are mainly found in the channels (Fig.…”
Section: Grain Sizesmentioning
confidence: 99%
“…The work of Fall et al (2021) is a helpful example for considering how to combine data from multiple instruments to better constrained poorly measured components of the floc fractal model. Additionally, Pearson et al (2021) recently developed a method to differentiate between components of the suspended mass associated with the sand and mud fraction by using a combination of sound and light scattering instruments. Comparison of data from such a system could help to better test and constrain the differentiated suspended mass from images making use of the sand and floc SVM segregation.…”
Section: Ssc Obtained From Imagesmentioning
confidence: 99%